Firearm-related suicides, homicides, and homicide-suicides involving security officers in two East African Countries: a press media revie - Muwanguzi, Moses; Kule, Moses; Nuwamanya, Simpson; Kaggwa, Mark Mohan (BMC psychiatry, 2023)
Background: Firearm violence is a growing public health problem causing death globally. With easy accessibility to firearms, suicides, homicides, and homicide-suicides have increased among security officers, especially in developing countries affected by long-standing civil wars/political insurgencies. No study has explored firearm violence in East African countries. This study describes the press media reporting of suicides, homicides, and homicide-suicides among security officers in two East African countries (Uganda and Kenya). Methods: Due to the absence of suicide databases among East African countries, the present study reviewed press media reports. We utilized content analysis of suicides, homicides, and homicide-suicides reports among security forces. Relevant media reports between January-2020 and May-2023 were searched. Using ANOVA and chi-square tests, we tested for statistical differences in characteristics between victims and perpetrators. Results: Among the 56 perpetrated reports, most of them were homicides 44.64% (n = 25/56), 30.36% (n = 17/56) were homicide-suicides, and 25% (n = 14/56) were suicides. Perpetrators’ age ranged from 21 to 47 years, majority being males [53/56 (94.64%)]. Victims were 58, mostly Ugandans [41/58 (73.21%)] with a mean age of 33.5 ± 8.81 years. Among the three main outcomes, statistically significant difference existed by country (χ2 = 23.88, p < 0.001), and perpetrators’ age (F = 8.59, p = 0.005). There was a significant difference between perpetrators and the number of victims lost by age of victims (F = 10.37, p = 0.002). Among victims, type of security of perpetrator and citizenship of victims (χ2 = 24.18, p < 0.001) showed statistical difference with Ugandans having more victims to army officers while Kenyans to police officers. Brief incident descriptions pointed towards relationship dysfunctions, alcohol/substance abuse, intentional harm, and financial disagreements, as the potential causes. Only two perpetrators were reported to have mental health-related conditions. Conclusion: This study shows that media reported firearms-related suicides, homicides, and homicide-suicides among security forces commonly involve males. Perpetrators in Uganda are mainly army officers while in Kenya the perpetrators are mostly police officers. Mental health conditions were not frequently reported among perpetrators. We recommend strengthening and enforcing gun regulation policies among security officers to curb this growing problem in these countries. Routine screening of mental health problems to enable early interventions is recommended among security officers.
Keywords: Suicide; Homicide; Uganda; Kenya; East Africa; Security officers; Gun violence; Firearms; Media report review